2021
DOI: 10.1016/j.bbih.2021.100361
|View full text |Cite
|
Sign up to set email alerts
|

Roles of calcitonin gene-related peptide in the skin, and other physiological and pathophysiological functions

Abstract: Skin immunity is regulated by many mediator molecules. One is the neuropeptide calcitonin gene-related peptide (CGRP). CGRP has roles in regulating the function of components of the immune system including T cells, B cells, dendritic cells (DCs), endothelial cells (ECs), and mast cells (MCs). Herein we discuss actions of CGRP in mediating inflammatory and vascular effects in various cutaneous models and disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 241 publications
(291 reference statements)
0
33
0
Order By: Relevance
“…A regulatory function of CGRP in the skin is known [ 19 ], and a case of severe wound healing disorder has also been described. It is suggested that impaired healing is caused by the inhibition of CGRP and consequently the absent downregulating effects of CGRP on the endothelial proinflammatory cytokines [ 8 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A regulatory function of CGRP in the skin is known [ 19 ], and a case of severe wound healing disorder has also been described. It is suggested that impaired healing is caused by the inhibition of CGRP and consequently the absent downregulating effects of CGRP on the endothelial proinflammatory cytokines [ 8 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SP potentiates the mechanisms and pathways triggering the translation of proteins and transcription factors involved in the switching (off and on) of the genes responsible for the cancer progression pathways. NK-1R inhibition by specific antagonists may be a novel strategy to control and manage the cancers [23,39]. SP binds to NK-1R and induces the activation of tumour pathways such as proliferation, invasion, angiogenesis, and migration of tumour cells to metastasize/metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of migraine there is also dura mater vasodilation. 2,15 Serotonin (5-HT) is considered a pain inhibitory agent and is one of the main neurotransmitters of the pain inhibitory pathway. In persistent pain model mice, 5-HT deficiency was associated with decreased thermal hyperalgesia and mechanical allodynia.…”
Section: Discussionmentioning
confidence: 99%